LAMINAR BOUNDARY LAYER FLOW OF NON-NEWTONIAN POWER LAW FLUID PAST A CONTINUOUSLY MOVING POROUS FLAT PLATE WITH SUCTION/INJECTION - Jadhav, Dr. B.P. (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
Laminar boundary layer flow of Non-Newtonian Power law fluid past a continuously moving porous flat plate has been considered. The governing equations of continuity and momentum are transformed into ordinary differential equations using similarity transformations. The equations are solved by using method of successive approximations starting with zeroth approximation. For n=1 the results tallies with Corresponding results for Newtonian fluids. Velocity profiles have been drawn for different values of parameter n; suction/injection parameter shows the behavior of power law fluids. Keywords: - boundary layer, power law fluids, successive approximations, suction/injection parameter, velocity profiles.